1988
DOI: 10.1002/em.2850110310
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cigarette smoking and solvent exposure on sister chromatid exchange frequency in painters

Abstract: A cross-sectional study of sister chromatid exchange frequency (SCE) in peripheral blood lymphocytes from 117 members of the International Brotherhood of Painters and Allied Tradesman was conducted in union locals in two major U.S. cities. Chronic solvent exposure intensity and duration were estimated from interviewer-administered-questionnaire data. SCE for all of the workers in the study were scored by one reader. A second reader determined the SCE frequency from a random sample of 30 workers. No significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Numerous studies have described the nature and source of toxic agents released into the environment. These include by-products of industrial processes [Pesonen and Anderson, 1992;Houk, 1992;Bucher et al, 1992;Adams et al, 1992;Nylund et al, 1994;Rank and Nielson, 19941, agricultural pesticides [Moutschen-Dahman et al, 1984;Madenjian et al, 1993;Welling and De Vries, 1994;Schlenk et al, 1992;Crane and Younghans-Haug, 19921, components of manufactured products [Poncelet et al, 1984;Hattemer-Frey et al, 1990;Kligerman et al, 1992;Das et al, 19941, combustion products [Hadnagy and Seemayer, 1987;Kelsey et al, 19941, food additives [Knudsen, 1986;Zeiger, 19931, and even derivatives of life-styles [Ghosh and Ghosh, 1988;Kelsey et al, 1988;Randerath et al, 1992;Stoichev et al, 19931. Major contaminants of the Great Lakes Basin have been identified and reported in a number of recent studies. For instance, Fabacher et al [I9911 have presented a detailed listing of the contaminants found in two Ohio rivers which empty into Lake Erie, two Wisconsin rivers which empty into Lake Michigan, and a Michigan river which empties into Lake Huron.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have described the nature and source of toxic agents released into the environment. These include by-products of industrial processes [Pesonen and Anderson, 1992;Houk, 1992;Bucher et al, 1992;Adams et al, 1992;Nylund et al, 1994;Rank and Nielson, 19941, agricultural pesticides [Moutschen-Dahman et al, 1984;Madenjian et al, 1993;Welling and De Vries, 1994;Schlenk et al, 1992;Crane and Younghans-Haug, 19921, components of manufactured products [Poncelet et al, 1984;Hattemer-Frey et al, 1990;Kligerman et al, 1992;Das et al, 19941, combustion products [Hadnagy and Seemayer, 1987;Kelsey et al, 19941, food additives [Knudsen, 1986;Zeiger, 19931, and even derivatives of life-styles [Ghosh and Ghosh, 1988;Kelsey et al, 1988;Randerath et al, 1992;Stoichev et al, 19931. Major contaminants of the Great Lakes Basin have been identified and reported in a number of recent studies. For instance, Fabacher et al [I9911 have presented a detailed listing of the contaminants found in two Ohio rivers which empty into Lake Erie, two Wisconsin rivers which empty into Lake Michigan, and a Michigan river which empties into Lake Huron.…”
Section: Introductionmentioning
confidence: 99%
“…In a group of 117 painters, no significant increase in sister chromatid exchange frequency was found (6). In addition, in a group of Swedish paint industry workers, Haglund et a1 (7) did not find a significant increase in sister chromatid exchanges or chromosome aberrations.…”
mentioning
confidence: 89%